Kajian Terapan Eko Interior Pada Rumah Turi Hotel di Surakarta - Soegijanto, Felita (Dimensi Interior, 2014)
Eco-interior is part of the eco-design which cover interior space and its occupants. The eco-interior aspects are organization of space, material selection, lighting systems, ventilation systems, indoor pollution, electromagnetic emissions, and waste management. These eight aspects of the study will be used as references for the analysis of applied eco-interiors on the object of research with eco-interior parameters. Rumah Turi was chosen as the object of this research because it is a building that already apply the principle of eco-friendly. How the eco-interiors principles are applied at Rumah Turi and how the classification of the principles are the issues that discussed in this study. This study uses qualitative research approach with case studies and descriptive method. The result of this study is the efforts and the classification of eco-interior applications at Rumah Turi. The classification shows the applied aspect that have been attempted to the maximum (organization of space, material selection, lighting systems in terms of energy conservation efforts, ventilation systems) and that have not been attempted to the maximum (substantial efforts: lighting systems in terms of occupants comfort, indoor pollution, and waste management; and light efforts: electromagnetic emissions).